MARKETING STRATEGY TO INCREASE SALES VOLUME IN S-MART SUPERMARKETS - Syamsuddin, Syamsuddin; Suriyanti, Suriyanti; Imaduddin, Imaduddin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to investigate the marketing strategies employed by S-Mart Supermarket to boost sales volume. The research methodology utilized is a qualitative descriptive approach. Primary and secondary data sources were utilized, with data collection techniques including interviews, observations, and documentation. The data analysis involved descriptive analysis, focusing on the 4P Marketing Mix concept (Product, Price, Promotion, Place). Additionally, a SWOT analysis was conducted to assess strengths, weaknesses, opportunities, and threats. This was followed by the creation of a Cartesian diagram to determine the company's sales position. The analysis revealed that S-Mart Supermarket has strategies in place to increase sales volume. These strategies include: Product Strategy: Offering a wide range of products to meet diverse customer needs. Price Strategy: Implementing competitive pricing by reducing profit margins. Distribution (Promotion) Strategy: Utilizing various promotional media such as banners, billboards, and radio advertisements to inform customers about promotional offers and prize draws. Place Strategy: Providing excellent customer service, including organized product displays and aesthetically pleasing store layouts. Based on the internal and external analyses, along with the Cartesian diagram conducted at S-Mart Supermarket, it was determined that the company is currently in a Growth strategy phase. The decision moving forward involves developing the business by enhancing product quality and variety and increasing various forms of promotions.